Monotone iterations for differential equations with a parameter. (1997) - Jankowski, Tadeusz; Lakshmikantham, V.
Abstract : Consider the problem { y ′ ( t ) = f ( t, y ( t ), λ ), t ∈ J = [ 0, b ], y ( 0 ) = k 0, G ( y, λ ) = 0. . Employing the method of upper and lower solutions and the monotone iterative technique, existence of extremal solutions for the above equation are proved.